The economics of derivatives - Somanathan, T. V.; Nageswaran, V. Anantha (New Delhi: Cambridge University Press, 2015)
"Discusses both the benefits and the drawbacks of derivatives trading and tries to take a broad view of both theory and practice"--
Includes bibliographical references and index.
Keywords: Derivative securities